Priority Tasks of Ensuring Religious Tolerance in Uzbekistan (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article considers priority directions of religious tolerance in Uzbekistan, including the experience of various developed countries to the phenomenon of religious tolerance, suitable suggestions and offers about ensuring both religious tolerance and freedom of conscience. Moreover there is also revealed some important key factors about implementing progressive condition for all the citizens of Uzbekistan on their inseparable right of religious and tolerance a.